Enhanced Electron Correlation in the In‐doped Misfit‐Layered Cobaltite Ca3Co4O9 Ceramics. Issue 3 (21st November 2012) - Huang, Yanan; Zhao, Bangchuan; Ang, Ran; Lin, Shuai; Huang, Zhonghao; Yin, Lihua; Tan, Shugang; Liu, Yu; Song, Wenhai; Sun, Yuping; Zhou, X.‐D.
<x xml:space="preserve">Abstract</x> The structural, magnetic, electrical and thermal transport properties of the polycrystalline samples Ca3Co4−xInxO9 (x = 0, 0.05, 0.10, 0.15, and 0.20) have been investigated systematically. The results indicate that the In‐substitution has a negative effect on the low‐temperature ferrimagnetic transition and the propagation of spin‐density‐wave. All In‐doped samples have a much larger resistivity than that of the un‐doped sample. And the temperature region where the Fermi liquid transport mechanism dominates is remarkably widened via In‐doping. However, for the In‐doped samples, as the In‐doped content increases, the value of resistivity ρ decreases monotonously and the electronic correlation in the system enhances. With the addition of In‐ions in Ca3Co4O9 system, the thermopower S and the ZT value decrease. The results are suggested to originate from the variations of carrier concentration and lattice disharmony in this system induced by In‐doping.